PROSPECTS FOR THE DEVELOPMENT OF FOREIGN INVESTMENT IN THE FIELD OF LAND RELATIONS IN UKRAINE (INNOVATIVE ECONOMY, 2020)
Kizyma T.O., Moroz V.V. PROSPECTS FOR THE DEVELOPMENT OF FOREIGN INVESTMENT IN THE FIELD OF LAND RELATIONS IN UKRAINEPurpose. The aim of the article is to study the current realities of the development of attracting foreign investments into the land relations of the domestic agricultural sector and developing practical recommendations and measures to improve the existing situation.Methodology of research. The methods of general scientific and empirical methods of economic science based on a systematic approach are used in the course of research, in particular: theoretical generalization (for studying the main problem points of attracting foreign investments into the agrarian sphere); comparison (to identify the positive and negative aspects that affect the investment advancement of the agrarian sector); abstract and logical method (to substantiate the prospects of building and developing directions of foreign investment in land relations in Ukraine).Findings. The factors of investment attractiveness of the domestic sphere of land relations are revealed on the basis of comparison of negative and positive sides of the given sphere from the point of view of foreign investors. The main problems of attraction of foreign investments, which are connected with the state policy in the part of reforming the agrarian sphere, are determined. The foreign experience in investing in land relations in the developed countries of the world is described.Originality. The modern trends of investment attractiveness of the domestic sphere of land relations are revealed, taking into account the current economic situation and the existing problem realities. The main ways of improving the investment attractiveness of the agrarian sector of Ukraine are outlined, taking into account the foreign experience and processes of urbanization, which has a global character of influence.Practical value. The obtained results of the research are the basis for developing the main directions of foreign investment in the sphere of land relations of Ukraine.Key words: investment; foreign investment; land relations; agrarian sector.
Keywords: Key words; investment; foreign investment; land relations; agrarian sector.